2018
DOI: 10.1155/2018/7493418
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Uron and Chlorobenzene Derivatives, as Potential Endocrine Disrupting Compounds, in the Secretion of ACTH and PRL

Abstract: Uron herbicides polluting the environment represent a serious concern for environmental health and may be regarded as endocrine-disrupting compounds (EDCs), which influence the regulation of human homeostasis. We aimed to investigate the effect of EDC urons (phenuron: PU, monuron: MU, and diuron: DU) and chlorobenzenes on the basal release of the adrenocorticotropic hormone (ACTH), which is a part of the adenohypophysis-adrenocortical axis. Hormone secretion in the presence of EDC was studied in two cell types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
5
0
2
Order By: Relevance
“…The effects of PU, MU, and DU added to the NH for 60 minutes at concentration of 10 −6 M were examined one by one [36]: PU CAS registry number: 101-42-8, DU CAS registry number: 330-54-1, and MU CAS registry number: 150-68-5 (Sigma, Germany). In our earlier studies, dose-dependent kinetics of phenylurea agents were determined, and the experimental doses were selected, because the saturation of receptor-binding sites depends on the affinity and number of receptor-binding molecules.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of PU, MU, and DU added to the NH for 60 minutes at concentration of 10 −6 M were examined one by one [36]: PU CAS registry number: 101-42-8, DU CAS registry number: 330-54-1, and MU CAS registry number: 150-68-5 (Sigma, Germany). In our earlier studies, dose-dependent kinetics of phenylurea agents were determined, and the experimental doses were selected, because the saturation of receptor-binding sites depends on the affinity and number of receptor-binding molecules.…”
Section: Methodsmentioning
confidence: 99%
“…In the outlined in vitro model, a primary ED effect has been demonstrated for the functioning of healthy and benign adenohypophysis cells in an essential function of ACTH release. As regards non-essential prolactin production, different secreted hormone levels were detected in the baseline interpretation of AdH versus PRLOMA cells (Table 4) (45).…”
Section: Figure 19 the Effects Of In Vivo Subtoxic Doses Of Chlorobenmentioning
confidence: 99%
“…was induced with AVP, which significantly increases ACTH release in healthy endocrine regulation (+ AVPAdH: 10220.88 ± 20.36), and is inhibited by corticosterone (B) (+ BAdH:1502.17 ± 3.25)(45). Studying the same control cycle with PRLOMA (+ AVPPRLOMA: 12674.50 ± 7.23; + BPRLOMA: 2155.50 ± 7.04), we found that the regulatory pattern persists but with slightly different ratios.…”
mentioning
confidence: 99%
“…α-MSH, β-MSH és γ-MSH, melyek eltérő affinitással kötődnek receptoraikhoz. MC-R-t a központi idegrendszeren kívül a perifériás szervekben (mellékvesekéreg, bőr, gasztrointestínum, pankreasz, vese, szív, tesztisz, ováriumok) A ClB-ok ösztrogénszerű hatásai is igazoltak [193,194], amelyen keresztül feltételezhetően az adenohipofízisben prolaktinomák kialakulásához [195], de a periférián vazokonstrikcióhoz is [196] vezethetnek. A ClB-ok jelentős ROS képzők [197].…”
Section: Avp éS Hálózati Kapcsolataiunclassified
“…A kísérleti (kontrollok és halogénezett és/vagy aromás -6 M) aktivált hormonvolumenek detektálása után, az adott kísérleti protokoll szerint önállóan (mClB, PU, MU, DU) és monoamin kombinációban (NA+mClB; NA+PU; NA+MU, NA+DU; 5-HT+mClB, 5-HT+PU, 5-HT+MU, 5-HT+DU) történt a kezelés (n=10/csoport). A protokollok szerinti kísérleti időpontokban történt a felülúszó médiumokból a mintavétel (500 µl) speciális műanyag csövekbe és a mérésig -70ºC-on tároltuk a mintákat[195]. (Immulite 2000, Siemens Healthcare Diagnostic, Deerfield, IL, USA, és DPC kit (L2KAC- 2; Euro/DPC Ltd, Glyn Rhonwy, UK) [39,195,225]).…”
unclassified